2022
DOI: 10.1007/s10815-022-02523-y
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2 pathogenetic variant carriers and reproductive decisions: Gender differences and factors associated with the choice of preimplantation genetic diagnosis (PGD) and prenatal diagnosis (PND)

Abstract: Purpose To investigate the way carriers of a BRCA1/2 pathogenetic variant make their reproductive decisions and to examine the factors associated with the choice of preimplantation genetic diagnosis (PGD) and prenatal diagnosis (PND). Methods We conducted a comprehensive literature search in PubMed, Scopus, and Web of Science in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…An income-related difference was also reported by Rich et al (12% of patients with income below 20 K $ were aware of the technique, compared to 38% of those with 20-50 K and 22% for >100 K $) [1]. Based on these data, it could be hypothesized that information is more accessible to higher-income classes; however, according to the authors, the motivation can also be attributed to different approaches by physicians [1,42].…”
Section: Knowledge Of Pgtmentioning
confidence: 63%
See 2 more Smart Citations
“…An income-related difference was also reported by Rich et al (12% of patients with income below 20 K $ were aware of the technique, compared to 38% of those with 20-50 K and 22% for >100 K $) [1]. Based on these data, it could be hypothesized that information is more accessible to higher-income classes; however, according to the authors, the motivation can also be attributed to different approaches by physicians [1,42].…”
Section: Knowledge Of Pgtmentioning
confidence: 63%
“…Regarding HBOC syndrome specifically, a review by Lombardi et al in 2022 confirmed higher levels of acceptability among male subjects [42]. Moreover, carrier status for HBOC syndrome correlated with a reduced desire for parenthood among female subjects, but not among male subjects.…”
Section: Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation